2007
DOI: 10.1148/radiol.2451061244
|View full text |Cite
|
Sign up to set email alerts
|

MR Colonography with Limited Bowel Preparation: Patient Acceptance Compared with That of Full-Preparation Colonoscopy

Abstract: Participants preferred MR colonography without extensive cleansing to colonoscopy immediately after both examinations and 5 weeks later. Experience of the bowel preparation and of the procedure was rated better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Achiam et al [2] used a five-point pain scale and indicated significantly greater discomfort during CC than MRC, a similar finding to Florie et al [4] who also grouped pain into five categories from ''none'' to ''extreme''. In our qualitative study, pain was mentioned more frequently with CC than MRC.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Achiam et al [2] used a five-point pain scale and indicated significantly greater discomfort during CC than MRC, a similar finding to Florie et al [4] who also grouped pain into five categories from ''none'' to ''extreme''. In our qualitative study, pain was mentioned more frequently with CC than MRC.…”
Section: Discussionmentioning
confidence: 68%
“…Patient acceptance is influenced by several factors, including test expectations, comfort, overall satisfaction and diagnostic performance. While it is assumed that patient acceptance of MRC is higher than colonoscopy, this is based on a limited number of studies [2][3][4][5][6][7]. For example, Achiam et al [2] reported that, in a cohort of 64 patients, 71% expressed preference for MRC as a future examination because it was less painful and unpleasant than CC.…”
mentioning
confidence: 99%
“…Although Mannitol was used in this study for clear visual confirmation of the effect of glucagon, the tagging sequence provides its own contrast and the method of motion sampling does not require bowel distention. Combined with the ability to sample motion during free breathing the low dependence on bowel preparation schemes will increase the patient acceptance of the method, as bowel preparation is often considered burdensome (19,20). Furthermore, bowel motion can be sampled during all motility periods related to the complete digestive process and during both wake and sleeping states with relative ease.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, MR colonography had a sensitivity of 93% and a specificity of 99% for polyp detection. In an MRC study of Florie et al (26) conducted through administering lactulose and gadolinium-containing oral contrast medium beginning from 48 hours prior to the study, the sensitivity was 77% in lesions 10 mm and above. The majority of studies in the past decade has focused on the role of dark-lumen MR colonography.…”
Section: Discussionmentioning
confidence: 99%